COVID-19 and household energy implications: what are the main impacts on energy use? - Cheshmehzangi, Ali (Elsevier, 2020)
This study explores the impacts of COVID-19 on household energy use. Some of these impacts are associated with longer-term energy demand changes and some could just be temporary. The study intends to present the results of a small pilot study conducted in China, by addressing household energy use. The samples are from 352 households and particularly focus on primary energy use in three periods of pre-pandemic (and pre-lockdown), start of COVID-19 outbreak and lockdown, and post lockdown. Each period is identified as a timeframe of 2.5 months, from November 2019 to late June 2020. The samples of this study highlight the primary implications of energy use, some that are understood as interim changes and some that may appear to be more prolonged. The results from the study highlight a variety of impacts on household energy use as well as prolonged impacts on transportation use. The primary household energy use are assessed in six fundamental elements of (1) transportation for commuting and leisure (for both private and public modes), (2) cooking, (3) entertainment, (4) heating and cooling, (5) lighting, and (6) the others. The results are summarized in three sections focused on major impacts on transportation use (comparison between private and public modes), cooking and entertainment, heating/cooling and lighting. The results could provide early suggestions for cities/regions that are experiencing longer lockdown. Furthermore, this study provides insights for larger-scale research in assessing household energy use/demand during times of health emergency and crises, such as the event of a pandemic.